Rheological Characterization of Poly(Ethylene Oxide) and Carboxymethyl Cellulose Suspensions with Added Solids - Osorio-Lira, F (Academic Press, 2015)
Many foods are suspensions of solid particles randomly distributed in a non-Newtonian polymeric fluid. The rheological properties of high molecular weight poly(ethylene oxide) (PEO) and carboxymethyl cellulose (CMC) suspensions by adding micro-metric solid particles such as fibres or spheres were studied. The particle volume fraction, Φ, was varied between 0 and 0.4. Their rheological properties were obtained after fitting a Cross model. Rheological behaviour of the solutions was compared with rheological behaviour of food reported in the literature. For PEO and CMC solutions with spherical particle, the behaviour of the normalized steady shear viscosity, μ/μ0, as function of the fraction volume was compared with a Thomas model. However, for PEO the multibody interactions were not well represented and for CMC suspensions, μ/μ0 seems to be lineal with Φ. To observe and explain more the influence of the particle concentrations on the rheological behaviour, dynamic rheological measurements (upon verification of the linearity limit) were also performed. A transition from a dominantly viscous fluid to a dominantly elastic material was observed when Φ was increased. © 2015 Elsevier Ltd.